The Role of Zakat, Infak and Shadaqah In Mitigating the Impact of Covid-19 Pandemic on Orphans In Indonesia - Rahmad Hakim; Arif Luqman Hakim (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2022)
This study aims to conduct an in-depth analysis of the role of Zakat, Infaq and Alms in Mitigating the Impact of the Covid-19 Pandemic specifically on Orphans in Indonesia. This type of research was qualitative with a case study approach. Interviews, observations and documentation were used as data collection techniques. Meanwhile, data analysis uses data content analysis. This research found that there was significant role of Zakat, Infaq and Almsgiving in Mitigating the Impact of the Covid-19 Pandemic specifically on orphans in Indonesia. The strategy carried out by the Malang City BAZNAS in distribution the scholarship was that the funds disbursed come from the State Civil Apparatus (ASN) infaq funds with 15% salary deductions for three months in 2021 to donate for the recipients of assistance scholarships due to the impact of covid-19 which was approximately 200 recipients of scholarship assistance due to the impact of covid-19. The contribution of this research was to provide a concrete picture regarding the role of Zakat, infaq and alms in realizing the concrete efforts of the Islamic philanthropy system in overcoming the impact of the Covid-19 pandemic in Indonesia.